Hydrothermal synthesis and photocatalytic application of ZnS-Ag composites based on biomass-derived carbon aerogel for the visible light degradation of methylene blue - Shanmugam, Paramasivam; Parasuraman, Balaji; Boonyuen, Supakorn; Thangavelu, Pazhanivel; AlSalhi, Mohamad S.; Zheng, Alvin Lim Teik; Viji, A. (Springer, 2024)
A facile and cost-effective hydrothermal followed by precipitation method is employed to synthesize visible light-driven ZnS-Ag ternary composites supported on carbon aerogel (CA). Extensive studies were conducted on the structural, morphological, and optical properties, confirming the successful formation of ternary nanocomposites. The obtained results evidently demonstrate the successful loading of ZnS and Ag onto the surface of the CA. High-resolution transmission electron microscopy analysis revealed that ZnS and Ag nanoparticles (AgNPs) were uniformly distributed on the surface of the CA with an average diameter of 18 nm. The biomass-derived CA, containing a hierarchical porous nano-architecture and an abundant number of –NH2 functional groups on the surface, can greatly prevent the agglomeration, stability and reduce particle size. Brunauer–Emmett–Teller analysis results indicated specific surface areas of 4.62 m2 g−1 for the CA, 48.50 m2 g−1 for the CA/ZnS composite, and 62.62 m2 g−1 for the CA/ZnS-Ag composite. These values demonstrate an increase in surface area upon the incorporation of ZnS and Ag into the CA matrix. Under visible light irradiation, the synthesized CA/ZnS-Ag composites displayed remarkably improved photodegradation efficiency of methylene blue (MB). Among the tested samples, the CA/ZnS-Ag composites exhibited the highest percentage of photodegradation efficiency, surpassing ZnS, CA, and CA/ZnS. The obtained percentages of degradation efficiency for CA, ZnS, CA/ZnS, and CA/ZnS-Ag composites were determined as 26.60%, 52.12%, 68.39%, and 98.64%, respectively. These results highlight the superior photocatalytic performance of the CA/ZnS-Ag composites in the degradation of MB under visible light conditions. The superior efficiency of the CA/ZnS-Ag composite can be attributed to multiple factors, including its elevated specific surface area, inhibition of electron–hole pair recombination, and enhanced photon absorption within the visible light spectrum. The CA/ZnS-Ag composites displayed consistent efficiency over multiple cycles, confirming their stable performance, reusability, and enduring durability, thereby showcasing the robust nature of this composite material.